A phenothiazine-based turn-on fluorescent probe for selective quantification of HClO in living cells. (June 2021) - Liang, Lijuan; Sun, Yimeng; Liu, Chang; Zeng, Xianshun; Zhao, Jianlong
Abstract: A simple phenothiazine-hemicyanine based probe PTZ-2Cy for selective in vitro and in vivo detection of ClO − was obtained. The detection mechanism was elucidated by absorption spectroscopy, emission spectroscopy, and ESI-MS analysis. With the increase in ClO − concentration, PTZ-2Cy first oxidize into sulfoxide product OPTZ-2Cy, and the additional concentration of hypochlorite ion leads to the cleavage of one or two CC bonds (OPTZ-Cy-CHO or OPTZ-2CHO ). This is accompanied by the color change from light pink to light yellow, absorption spectra shift from 580 to 493 nm, and significant enhancement of fluorescence emission at 595 nm. The low limit of detection of ClO − ions (LOD = 0.038 μM) was obtained for the PTZ-2Cy probe in the 0–20 μM concentration range. The probe shows excellent selectivity for ClO − ions owing to dual-wavelength fluorimetric detection at 488 and 600 nm. The probe is applicable for imaging HClO in L929 cells and is a promising candidate for the development of a fluorescence sensor for hypochlorite ions detection in biological samples. Graphical abstract: A simple phenothiazine-hemicyanine based probe PTZ-2Cy was developed. The probe shows excellent selectivity for hypochlorite (ClO − ) ions owing to dual-wavelength fluorimetric detection at 488 and 600 nm. The probe is applicable for imaging ClO − ions in L929 cells. Image 1 Highlights: A simple phenothiazine-hemicyanine based probe PTZ-2Cy for selective in vitro and in vivo detection of ClO − was obtained. The detection mechanism was elucidated by absorption spectroscopy, emission spectroscopy, and ESI-MS analysis. The low limit of detection of ClO − ions (LOD = 0.038 μM) was obtained for the PTZ-2Cy probe in 0–20 μM concentration range.